Breadth and depth of promotional sales in food retailing - Thomas Glauben; Kristin Hansen; Jens-Peter Loy; Christoph R. Weiss (Agricultural Economics (Zemědělská ekonomika), 2011)
Temporary price reductions (sales) as a means of promotion have become an increasingly important tool in the marketing mix of food retailers around the world. This paper investigates the retailers' pricing strategy by explicitly accounting for the multi-product nature of retailing. We find that retailers systematically adjust the breadth and depth of sales over time and they respond aggressively to their rivals' promotional activities. Finally, the breadth and depth of sales are found to be substitutes in the set of the available strategies to increase the store traffic. – – Dočasná snížení cen (slevové prodeje) se jako způsob propagace stávají stále významnějším nástrojem marketingového mixu maloobchodních prodejců potravin na světové úrovni. Práce zkoumá cenovou strategii maloobchodních prodejců se specifickým důrazem na multiproduktový charakter maloobchodu. Výzkumem bylo zjištěno, že maloobchodní prodejci systematicky upravují šířku a hloubku slev v průběhu času a že agresivním způsobem reagují na propagační aktivity svých konkurentů. Bylo zjištěno, že šířka a hloubka prodejních slev jsou subsituty v systému dostupných strategií zvýšení obratu zásob.
Keywords: 330; multi-product food retail pricing; promotional sales; Germany; milk products